Economic Evaluation of Three Available Solutions for Promotion of Wind Power Integration - Hong-Kun Chen; Yan-Juan Yu; Lei Chen; Xin Jiang; Ren-Yan Yu (International Journal of Rotating Machinery, 2017)
The limited operational flexibility of combined heat and power (CHP) units is the main cause of wind power curtailment in the thermal-electrical power system of Northern China. Pumped hydrostorage (PHS), heat storage (HS), and electric boiler (EB) are investigated as three alternative options for the promotion of wind power integration. On the basis of two linear models that determine the capacities of these three facilities required for integrating the curtailed wind power, economic evaluation in terms of investment costs and environmental benefits is presented. Analysis results show that HS requires the least investment and has a good performance of coal saving when accommodating the same amount of curtailed wind power. And EB has the greatest potential for wind power integration with the huge growth of installed capacity of wind power in the future.